Nitric oxide generation in response to intense physical exercise = Generacja tlenku azotu w odpowiedzi na intensywny wysiłek fizyczny - Morawin, Barbara; Kalina, Karol; Rynkiewicz, Mateusz; Zembroń-Łacny, Agnieszka (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Nitric oxide (NO), as a signaling molecule, plays a key role in the reconstruction of muscle fibers, especially in the early phase after injury, initiating the proliferation of muscle stem cells (satellite cells), angiogenesis and synaptogenesis in motor neuron axons, and, as a result, an increase in the strength of muscle contraction. The study was designed to explain whether a single exercise trial increases NO generation and whether changes in NO level are related with skeletal muscle damage and body composition in non-athletes.
Keywords: tlenek azotu; mioglobina; skład ciała; uszkodzenie mięśni; wysiłek fizyczny; nitric oxide; myoglobin; body composition; muscle damage; physical exercise